Sistem Administrasi Kependudukan dan Inventarisasi Desa Kulu Kabupaten Pekalongan Menggunakan Borland Delphi 7.0 - Aslam Fatkhudin (LPPM Universitas Al Asyariah Mandar, 2016)
Kulu village head's office is a government agency which serves airport administration and inventory for the village people associated with the elements of geographical, social, economic, political, and cultural as well as interconnected with other areas.Technological developments in Village Head Office Kulu been computerized but has not had an application program that can assist employees in carrying out and run the job.Development and technological progress is urgently needed now in Kulu Village Head Office to support and improve the quality in providing services to the public.Steps being taken in this research is data collection is done based on field studies, namely through observational studies, a review is carried directly to the administrative section and the inventory in the village hall kulu. Development of systems using object-oriented analysis with the waterfall method, followed by the design which includes process design, database design, and user interface.Implementation of the design is the result of encoding by using a programming language that has been set.The result is Application Administration and Inventory Population System at Village Head Office Kulu Using Borland Delphi 7.0.This application was developed using information technology-based computer applications with MySQL database